Fragile X mental retardation protein is involved in protein synthesis-dependent collapse of growth cones induced by Semaphorin-3A - Li, Chanxia; Bassell, Gary j.; Sasaki, Yukio (Frontiers in Neural Circuits, 2009)
Fragile X syndrome, the most frequent form of familial mental retardation, is caused by mutation of the Fmr1 gene. Fmr1 encodes the Fragile X Mental Retardation Protein (FMRP), an mRNA binding protein regulating local, postsynaptic mRNA translation along dendrites necessary for long-term synaptic plasticity. However, recent studies on FMRP localization in axons and growth cones suggest a possible function in the regulation of local protein synthesis needed for axon guidance. Here, we have demonstrated that FMRP is involved in axonal and growth cone responses induced by the axon guidance factor, Semaphorin-3A (Sema3A). In cultured hippocampal neurons from wild type mice, Sema3A-induced growth cone collapse was protein synthesis-dependent. In contrast, Sema3A-induced growth cone collapse was attenuated in Fmr1 knock-out (KO) neurons and insensitive to protein synthesis inhibitors, suggesting that FMRP is involved in protein synthesis-dependent growth cone collapse. Sema3A increased phosphorylation of eukaryotic initiation factor 4E (eIF4E), an indicator of local translation, in distal axons and growth cones of wild type, but not Fmr1 KO neurons. Furthermore, Sema3A rapidly induced a protein synthesis-dependent increase in levels of microtubule associated protein 1B (MAP1B) in distal axons of wild type neurons, but this response was attenuated in Fmr1 KO neurons. These results suggest a possible role of FMRP to regulate local translation and axonal protein localization in response to Sema3A. This study reveals a new link between FMRP and semaphorin signaling in vitro, and raises the possibility that FMRP may have a critical role in semaphorin signaling in axon guidance during brain development.